DELAY IN DEVELOPMENT AND INCLUSION: THE OPINION OF PROFESSIONALS OF THE NURSERY - Frigieri de Vitta, Fabiana Cristina [UNESP]; Mouro, Mariana Martins [UNESP]; Ribeiro Sgavioli, Ana Julia [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
The objective of this research was to verify the the opinion of professional who works on children's education institutions about the function of nursery in relation to developmental difference of children at this stage. An interview were answered for 17 professional of an institution linked to the Municipal Department of Education of a medium-sized city in the Paulista countryside. The results shows that the nursery, receiving very young children, is a propitious place to identify the the developmental difference and favorable to offer intentional activities hat can improve the quality of the baby's full development. The resulting difficulties of the inappropriate formation should be considerate to the nursery allow all the child to enjoy a stimulate ambiance who comply the fundamental right of quality education.
Keywords: Children's Education; Inclusive Education; Nursery; Developmental Delay